2011
DOI: 10.1016/j.diagmicrobio.2011.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Dengue nonstructural protein 1 antigen in the urine as a rapid and convenient diagnostic test during the febrile stage in patients with dengue infection

Abstract: A total of 136 matched serum and urine samples obtained from 55 patients with dengue infection and 30 other febrile illnesses were assayed for dengue nonstructural protein 1 (NS1) antigen. The urine NS1 ELISA was positive in patients with dengue fever (68.4%) and dengue hemorrhagic fever (63.9%), whereas the strip method showed a lower positive rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…In a previous study, the NS1 antigen was detected in urine samples collected on days 2-10 after disease onset, positive rates of NS1 antigen using NS1 antigen ELISA were 68.4z and 63.9z in 19 DF and 36 DHF samples, respectively (21). However, the utility of NS1 antigen ELISA was not determined at each disease phase.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a previous study, the NS1 antigen was detected in urine samples collected on days 2-10 after disease onset, positive rates of NS1 antigen using NS1 antigen ELISA were 68.4z and 63.9z in 19 DF and 36 DHF samples, respectively (21). However, the utility of NS1 antigen ELISA was not determined at each disease phase.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies by other investigators have shown the presence of viral genome in the urine samples of dengue patients (12,20). Additionally, NS1 antigen has been detected in urine samples from days 2-10 after the onset of the disease (21). However, determining the applicability of NS1 ELISA at each phase of the disease would confirm the usefulness of NS1 antigen detection in urine samples for DENV diagnosis.…”
Section: Introductionmentioning
confidence: 87%
“…These patient samples were collected from 17 countries in Latin America, Asia and Oceania, and the most studies were conducted in Brazil (27%) [29], [34], [37], [41], [45], [47], [52], [54], Vietnam (13%) [32], [33], [36], [49], Malaysia (13%) [26], [36], [42], [46] and Thailand (13%) [31], [36], [43], [48]. Regarding the design of the studies, they were classified into two types: prospective and retrospective cohorts, of which only twelve reported that their samples were collected during dengue outbreaks [25], [26], [30], [37], [39], [40], [44], [45], [51][54].…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis of other viral infections in urine and saliva samples has been reported for human immunodeficiency virus (HIV), Hepatitis A, B, and C, and rubella [14][15][16][17][18][19][20], and more recently in other flaviviruses, West-Nile virus (WNV) [21][22][23] and Dengue (DENV) serotypes -1, -2, -3, and -4 [24][25][26][27][28][29][30][31][32][33][34][35]. WNV can be detected longer in urine than serum [21] and can be isolated from urine [22,23].…”
Section: Advantages Of Non-invasive Sample Collectionsmentioning
confidence: 99%